Sabbath Observance during the Second Jewish Revolt (132–135/6 CE): A Re-examination - Bourgel, Jonathan (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2025)
The discovery of the Bar Kokhba letters in the Judean Desert has provided invaluable insights into the structural, organizational, and administrative aspects of the short-lived state under the leadership of Shimʿon Bar Kosiba (132-135/6 CE). Numerous documents in this collection address the observance of religious commandments; two letters, P.Yadin 50 (= 5/6Ḥev 50) and Mur 44, specifically emphasize the observance of the Sabbath. The purpose of this study is to show that these letters not only underscore the meticulousness of Bar Kosiba and his followers concerning religious matters associated with the Sabbath, but also shed light on the difficulties of adhering to its observance amidst wartime circumstances. Drawing on an analysis of these letters, alongside literary sources and archaeological discoveries related to the Second Revolt, the article also investigates the likely position of Bar Kosiba’s adherents on this complex issue.